2022
DOI: 10.1111/jfbc.14149
|View full text |Cite
|
Sign up to set email alerts
|

Zingerone ameliorates non‐alcoholic fatty liver disease in rats by activating AMPK

Abstract: This study was conducted to test the protective potential of Zingerone against a highfat diet (HFD)-mediated non-alcoholic fatty liver disease (NAFLD) development in rats and examined in this protection is mediated modulating AMP-activated protein kinase (AMPK). Animals were segregated based on their diet and treatment into four groups (n = 6 each): (a) fed standard diet (STD), (b) treated with Zingerone (100 mg/kg), (c) fed HFD, (d) HFD + Zingerone (100 mg/kg), and (e) HFD + Zingerone (100 mg/kg) + compound c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…In vivo zingerone activates PPAR-α [ 57 ]. It is therefore possible that it exerted its antisteatotic effects by preventing the downregulation of PPAR-α Additionally, previous research had found that zingerone can suppress the expression of SREBP1c [ 33 ] to protect against fatty liver formation and lipid accumulation therefore our findings are in tandem with other research outcomes.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In vivo zingerone activates PPAR-α [ 57 ]. It is therefore possible that it exerted its antisteatotic effects by preventing the downregulation of PPAR-α Additionally, previous research had found that zingerone can suppress the expression of SREBP1c [ 33 ] to protect against fatty liver formation and lipid accumulation therefore our findings are in tandem with other research outcomes.…”
Section: Discussionsupporting
confidence: 77%
“…Several pharmacological agents have proven effective as potential prophylaxes in managing adverse effects induced by exposure to toxic substances during periods of developmental plasticity [ 32 , 33 , 34 ]. Zingerone has been reported to possess antisteatotic properties that can protect against the development of fatty liver via the activation of AMP-activated protein kinase (AMPK) [ 33 , 35 ]. Furthermore, oral supplementation of 40 mg/kg body wt of zingerone via intragastric intubation to alcohol-fed Wistar rats protected against hepatoxicity [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mohammed (2022) found that the activation of AMPK signaling pathway reduced hepatic oxidative stress, in ammation, and apoptosis in NAFLD. The phosphorylation of AMPK enhanced the activities of GSH and SOD, depleted MDA concentration, and enhanced NRF2 level [44]. AMPK signaling pathway exerts hepatoprotective effect against concanavalin A-induced hepatitis in mice [45].…”
Section: Discussionmentioning
confidence: 94%
“…PMS was bought from Sigma (PHL83304, St. Louis, MO, USA) with a purity of ≥95.0% (HPLC). Rats in HFD + 80 mg/kg PMS + CC group were intraperitoneally injected with 80 mg/kg PMS and intragastrically administered with the inhibitor of AMPK pathway compound C (CC, 0.2 mg/kg) (P5499, purity≥98% [HPLC], Sigma) 18 once a day for 4 weeks. At the end of experiment, rats were weighed, and then intraperitoneally injected with sodium pentobarbital (100 mg/kg) for sacrifice.…”
Section: Methodsmentioning
confidence: 99%
“…[HPLC], Sigma) 18 once a day for 4 weeks. At the end of experiment, rats were weighed, and then intraperitoneally injected with sodium pentobarbital (100 mg/kg) for sacrifice.…”
Section: Animal Treatmentmentioning
confidence: 99%